Using Crossword Puzzle Game to Improve Students' Vocabulary Mastery - Siregar, Yunita Permata Sari; Harida, Eka Sustri; Siregar, Sri Rahmadhani (English Education : English Journal for Teaching and Learning, 2024)
This study aims to improve students’ vocabulary mastery by using crossword puzzle game at grade VII students of SMP N 5 Padangsidimpuan. Because it has found in that school the students’ vocabulary mastery is still low. The method used is Classroom Action Research. The participants of this research were 23 students in class VII-5 SMP N 5 Padangsidimpuan. The data analyses were from vocabulary test, observation notes and interview. The result of the research showed the improvement mean score of the students. The first test in the first cycle was 60.17 and second test in the second cycle was 82.60. It can be concluded that the mean score in the second cycle was higher than the first cycle. Based on observation notes stated that the students got improvement of vocabulary and the students were more active and interested in learning vocabulary mastery. Related to the interview result, it could be known that students’ vocabulary mastery had improved. It asserted that crossword puzzle game can improve students’ vocabulary mastery at grade VII-5 SMP N 5 Padangsidimpuan. The result in the previous study increased 17.05 while in this study The novelty of this research is from the improvement increased 22.43.